Daylighting Performance in an Atrium with ETFE Cushion Roof and in an ETFE-Encapsulated Panel Structure. (November 2015) - Masih, Dawa Azad Aziz; Lau, Benson; Chilton, John
Abstract: This paper presents the results of the field work on the luminous environment conducted in an atrium enclosed by an ethylene-tetra-fluoro-ethylene (ETFE) cushion roof and a test structure constructed with ETFE-encapsulated panels. In addition to the on-site monitoring, theoretical parametric studies using a scaled physical model of the ETFE panel structure were undertaken to further investigate the lit environment created by changing the transparency of the test structure envelope. The aim is to explore how the typical homogeneous and dull luminous environment can be improved. Subjective appreciation of the lit scenes and quantitative analysis results are compared and discussed. This study concluded that selective use of translucent and opaque components in the ETFE enclosures can offer opportunities to create well balanced, yet dynamic lighting conditions. Also selective positioning of these components in different parts of the ETFE structures can help improve modelling effect and enhance visual perception.